ADVANTAGES AND CHALLENGES OF THE BLENDED LEARNING APPROACH: ADVANTAGES AND CHALLENGES OF THE BLENDED LEARNING APPROACH - Ismaylova, Shakhnoza (Журнал иностранных языков и лингвистики, 2025)
Over the past two decades, the landscape of education has undergone a dramatic transformation due to technological advancements and the changing needs of learners. Among the most significant developments is the rise of blended learning—a teaching model that combines traditional in-person instruction with online learning experiences. Blended learning, also referred to as hybrid learning, offers a flexible and interactive alternative to purely face-to-face or fully online education. It has gained widespread adoption in higher education, K-12 schools, and corporate training environments.